Finite Element Stress and Fatigue Analysis of Buried Steam Distribution Pipelines for District Heating in Philadelphia - Desmond Ondieki Ocharo; Victoria Bukky Ayoola (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This study presents a comprehensive finite element investigation of stress distribution, fatigue life, and deformation behavior in buried steam distribution pipelines serving Philadelphia’s district heating network. Aging pipelines in urban environments are subjected to complex loading conditions, including thermal cycling, internal pressure, soil–pipe interaction, and geometric discontinuities, all of which significantly influence long-term structural integrity. The analysis reveals that weld joints, elbows, and fixed support locations experience the highest stress concentrations due to multi-axial loading and constrained thermal expansion. Fatigue life predictions show accelerated crack initiation in areas where thermal gradients and soil stiffness variations overlap, particularly in neighborhoods with soft clay soils and shallow-burial installations. Field inspection images corroborate the numerical findings by showing visible cracking and deformation in high-stress regions. Thermal cycling emerged as the dominant fatigue driver, while insulation effectiveness proved crucial in moderating deformation severity. A combined evaluation of soil conditions and operational temperature fluctuations highlights the need for targeted engineering interventions. Recommendations include reinforcement of critical sections, improved insulation strategies, soil stabilization, and deployment of real-time monitoring systems such as fiber-optic strain sensing and thermal imaging. The study’s findings provide actionable insights for district heating operators, emphasizing the importance of risk-based asset management and integration with smart city monitoring frameworks. Overall, this research enhances understanding of the failure mechanisms governing buried steam pipelines and offers practical guidance to improve reliability, safety, and long-term performance within Philadelphia’s district heating infrastructure.